Papanicolaou smear in pregnant women: a prospective study - Niyaf NA; Bhavya HU; Ravikanth GO; Geeta J Doppa (Barpeta Obstetrics and Gynaecological Society, 2022)
Objectives: Aim of the study is to assess the prevalence of abnormal pap smear in pregnant women and its associated risk factors. Methods: This is a prospective observational study, 200 pregnant women were recruited who came for regular antenatal visit. Papanicolaou smear was done as per conventional method and reported using 2014 Bethesda system. Results: 53.6% of pregnant women had abnormal pap smear. Among them, 29% had inflammatory smears, 9% had bacterial vaginosis, 3% showed trichomonal and 7% monilialiasis. The abnormal smears were more in patients from rural background (58.5%) than urban (29%), which is statistically significant. Most of them in lower class (88.8%) had abnormal pap. The frequency of abnormal pap in illiterates was 83.3%, 64.7% in middle school, in senior secondary it was 50.7% and graduates was 37.83%. There were 86.5% abnormal smears in those < 21 years of age at first intercourse as compared to 33.06% in those ≥ 21 years of age and the difference was statistically significant. There were 4 (80%) abnormal smears among those with more than one sexual partner as compared to 1(20%) normal smear. 26 (30.58%) abnormal smears in primigravida and 74 (67.88%) abnormal smears in multigravida was noted which was statistically significant. Conclusion: Clinicians should make every effort to educate, counsel and screen pregnant women if they have not had a pap test in the past in order to reduce the burden of cervical cancer in our country. This opportunity for screening cervical cancer should not be missed in the antenatal period.